'The Surest of All Morale Barometers': Transnational Encounters in the XV International Brigade. (February 2022) - Raeburn, Fraser
Abstract : Despite considerable scholarly and popular interest in the International Brigades, which fought on the side of the Spanish Republic during the Spanish Civil War of 1936–9, traditional approaches centred on 'national' contingents of foreign volunteers have left significant gaps in historical knowledge. In particular, relations between the foreign volunteers and their Spanish hosts have received little attention, even though these relationships were fundamental to the everyday experience of volunteering, as well as affecting the International Brigades' cohesion during their time in Spain. This account introduces a range of new archival material relating to the English-speaking XV International Brigade, arguing that pervasive structural and cultural factors led to a complex and variable set of outcomes that defy binary categorisation. In doing so, this study contributes to an emerging new literature on transnational approaches to the Spanish Civil War and interwar anti-fascisms, as well as comparative approaches to foreign fighter mobilisations.